Análise dos efeitos tributários do Programa Universidade para Todos (PROUNI): estudo de caso - Feitosa, Marilene (2007)
The complexity of the Brazilian tax legislation has increased the necessity of the Institutions to organize its businesses under the focus of the tributary planning, in the intention to reduce the tax burden. The Law n.° 11,096, of January 13th, 2005, that it instituted the "University for All Program" (PROUNI), inserted the exemption of some federal tributes in exchange for integral and partial scholarships granted by the Institutions of Superior Education for low income young students. This work had as objective to evaluate the tributaries effects observed in a Private Institution of Superior Education, with lucrative ends, situated in the City of Fortaleza, function of the adhesion to the "University for All" Program (PROUNI), to describe the tributes related with the program and to relate the tax economy reached with the investment supported with scholarships granted in the scope of the PROUNI. The methodology was based on documentary and bibliographical research, using of the method study of only case. Some sources of evidence had been used (interviews, countable demonstrations, financial reports, spread sheets of tribute verifications and documents related with the program). The gotten results demonstrate that the Private Institution of Superior Education analyzed recouped all the tributes related with the PROUNI, leaving to collect to the State the equivalent to, on average, 53% of the total of tributes it had, representing 4% of its invoicing. It has been distinguished that the program significantly extended the vacant number in the superior education, disconcentrated the gratuitous education and contributed to fight the social inaquality.